The use of organising purposes in science instruction as a scaffolding mechanism to support progressions: a study of talk in two primary science classrooms. Issue 1 (2nd January 2018) - Johansson, Annie-Maj; Wickman, Per-Olof
Abstract: Purpose: This study examines how different purposes can support teachers in their work with progressions as a part of a teaching sequences in science in primary school. Design/Method: The study was carried out in two classes working with inquiry and the events that took place in the classroom were filmed. In the study, we have chosen to use the technical term proximate purposes for the student-oriented purposes, and ultimate purposes for the scientific purposes. Together, these two types of purposes form the organisational purposes for the classes. Proximate purposes work in such a way that students can use their language and relate to their experiences as ends-in-view. To examine how organising purposes can be used to analyse progressions, we discuss examples from two different lessons. Result: The study shows the importance of proximate purposes working as ends-in-view and also demonstrates how the teacher and students may create continuity in teaching to enable progression as a part of a teaching sequence. Conclusions: To create continuity, it was essential that the teacher scaffolded the students in ways which allowed the students to explicitly differentiate between what was relevant or not, about the proximate purposes in relation to the ultimate purpose.